Exploring the patient's recovery journey and information needs following a shoulder fracture: A qualitative interview study. - Pauline May; Firoza Davies; Gillian Yeowell; Chris Littlewood (PLoS ONE)
Background Shoulder fractures (proximal humerus fractures) are common, painful, debilitating injuries. Recovery is a long process often hindered by complications such as mal-union and frozen shoulder. The purpose of this qualitative study was to explore the experiences and information needs of people at different time points after a shoulder fracture and how views on recovery change over time. Methods This longitudinal telephone interview study used a semi-structured approach based on a pre-planned interview topic guide. Recruitment was from June to November 2023. Participants were interviewed approximately two months and five to six months after their injury. Interviews were audio-recorded and transcribed verbatim. Data were analysed using thematic analysis. Results 14 participants were recruited (age range 44-80 years; three male). The themes identified were dependence, vulnerability, information needs, and recovery. Loss of function and identity were associated with dependence. Feelings of vulnerability were present for most participants at six months post-injury. Information needs evolved, with information about the extent of the injury and practical advice needed first, but later participants emphasized the importance of reassurance and expected timelines for recovery. Recovery meant regaining function and independence, and returning to meaningful activities, which was also not fully achieved for most participants by six months. Conclusions This study is the first to explore information needs and experiences along the timeline of recovery from a shoulder fracture. What recovery means to individual patients, along with recognition of the extent to which feelings of vulnerability affect recovery are important factors to consider. Clinicians should be aware of the full impact of these injuries to guide patients on their recovery journey, including identifying feelings of vulnerability and regaining their identity. Adopting a person-centred care approach, and considering the changing priorities and information needs of patients throughout their recovery journey may lead to improved patient care.